A T cell receptor antagonist peptide induces T cells that mediate bystander suppression and prevent autoimmune encephalomyelitis induced with multiple myelin antigens - Nicholson, Lindsay B. (The National Academy of Sciences of the USA, 1997)
Experimental autoimmune encephalomyelitis (EAE) induced with myelin proteolipid protein (PLP) residues 139–151 (HSLGKWLGHPDKF) can be prevented by treatment with a T cell receptor (TCR) antagonist peptide (L144/R147) generated by substituting at the two principal TCR contact residues in the encephalitogenic peptide. The TCR antagonist peptide blocks activation of encephalitogenic Th1 helper cells in vitro, but the mechanisms by which the antagonist peptide blocks EAE in vivo are not clear. Immunization with L144/R147 did not inhibit generation of PLP-(139–151)-specific T cells in vivo. Furthermore, preimmunization with L144/R147 protected mice from EAE induced with the encephalitogenic peptides PLP-(178–191) and myelin oligodendrocyte protein (MOG) residues 92–106 and with mouse myelin basic protein (MBP). These data suggest that the L144/R147 peptide does not act as an antagonist in vivo but mediates bystander suppression, probably by the generation of regulatory T cells. To confirm this we generated T cell lines and clones from animals immunized with PLP-(139–151) plus L144/R147. T cells specific for L144/R147 peptide were crossreactive with the native PLP-(139–151) peptide, produced Th2/Th0 cytokines, and suppressed EAE upon adoptive transfer. These studies demonstrate that TCR antagonist peptides may have multiple biological effects in vivo. One of the principal mechanisms by which these peptides inhibit autoimmunity is by the induction of regulatory T cells, leading to bystander suppression of EAE. These results have important implications for the treatment of autoimmune diseases where there are autopathogenic responses to multiple antigens in the target organ.